Dimensions of Education Services in Perspective Thematic Interpretation of the Qur'an - Muhajir, As'aril (AL-IDARAH: JURNAL KEPENDIDIKAN ISLAM, 2021)
This article is intended to examine the service dimension in the Quranic interpretation to gain a comprehensive and in-depth understanding of the realization of a superior and competitive educational institution. The values of service contained in the Qur'an, the Hadith and the sources of civilization in the past can be a perfect and differentiator of secular concepts and theories that are now established. Thus, the quality of educational services within the framework of Islam can be the competitive advantage of Islamic education service organizations. The quality of education services in Islamic concepts has two aspects: business orientation and worship orientation. Providing educational services that will provide the first appraisal is Allah SWT, and the following party who gives the judgment is human. Keywords: Educational Services, Thematic Interpretation